The Influence Of Booklet Media In Increasing Maternal Knowledge On The Growth And Development Of Toddlers Aged 1-5 Years - Az-Zahra, Siti Fathimah; Iriyani, Elfrida (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2024)
The number of delays in growth and development in Indonesia is still high, around 5-10% have delays in growth and development in general. Child development is influenced by several factors and one of them is maternal knowledge. In Posyandu Johar Sari mothers of toddlers have insufficient knowledge about the growth and development of their children. The purpose of this research was to determine the influence of booklet media in the increasing of maternal knowledge on the growth and development of toddlers. The type of quantitative research with Pre-Experiment method and research design using one group Pretest then Post-test. The number of samples of 28 mothers was determined from purposive sampling. Data collection using questionnaire sheet. Data analysis using SPSS software with wilcoxon test and the results p value of 0.000 or p<0.00. The result shows that there is an influence of booklet media in increasing maternal knowledge on toddler growth and development